Factors Affecting Intratympanic Corticosteroids Injection Therapy Results in Sudden Deafness Patients at Dr Mohammad Hoesin Hospital Palembang - Abla Ghanie; Listya Paramita; Fiona Widyasari; Ahmad Hifni; Erial Bahar (HM Publisher, 2021)
Background. Sudden deafness is an emergency in the Ear Nose Throat Department, a subset of sensorineural hearing loss within a 72-hour window period and consists of a decrease in hearing of 30 decibels affecting at least three consecutive frequencies. The therapy given is corticosteroids, systemic corticosteroids or intratympanic corticosteroids injection, or both. The prognosis of sudden deafness depends on several factors. Patient with sudden hearing loss does not always have the same result in hearing improvement. This study was aimed to determine the factors that affect the results of intratympanic corticosteroid injection therapy in patients with sudden deafness.Methods. This study is an observational study with a cross-sectional design. The data were collected using medical records on 96 ears given intratympanic corticosteroid injection therapy at Dr. Mohammad Hoesin Hospital Palembang from July 2018 to February 2021.Results. From 96 ears conducted in the study, the improvement of therapeutic results on intratympanic corticosteroid injection in patients with sudden deafness was 72.9%. The study found factors that influenced the outcome of therapy, namely age (p=0.002), the onset of therapy (p = 0.003), and the use of a combination of systemic steroids (p=0.010). From the logistic regression test, it was found that the factors that most influenced the results of intratympanic corticosteroid injection therapy were young age 18-40 years (p=0.016) with (OR) 6.654 (CI95% 1.418-31.222) and therapy onset less than two weeks (p=0.027) with (OR) 3.108 (95% CI 1.134-8.515).Conclusions. The factors associated with the improvement in the outcome of intratympanic corticosteroid injection therapy in patients with sudden hearing loss were patient age and early onset of therapy.